Decline in Emotional Face Recognition Among Elderly People May Reflect Mild Cognitive Impairment - Ochi, Ryuta; Midorikawa, Akira (Frontiers in Psychology, 2021)
As with cognitive function, the ability to recognize emotions changes with age. In the literature regarding the relationship between recognition of emotion and cognitive function during aging, the effects of predictors such as aging, emotional state, and cognitive domains on emotion recognition are unclear. To clarify which cognitive functions affect the recognition of emotion and whether depression also has effects, we analyzed these factors using multiple linear regression analyses and a multicomponent cognitive test. In all, 26 young (mean age = 20.9 years) and 30 elderly subjects (71.6 years) participated in the study. All subjects participated in face-perception, face-matching, emotion-matching, and emotion-selection tasks. In addition, elderly subjects were administered the Neurobehavioral Cognitive Status Examination (Cognistat) and the Geriatric Depression Scale-Short Version. There were no significant differences between the two groups in the face-perception task, but in the face-matching, emotion-matching, and emotion-selection tasks, elderly subjects showed significantly poorer performance. Among elderly subjects, multiple regression analyses showed that performance on the emotion-matching task was predicted by age, emotional status, and cognitive function, but paradoxical relationships were observed between recognition of emotional faces and some verbal functions. In addition, 47% of elderly participants showed cognitive decline in one or more domains, although all of them had total Cognistat scores above the cutoff. Thus, it might be crucial to consider preclinical pathological changes such as mild cognitive impairment when testing for age effects in elderly populations.